2016
DOI: 10.1111/1462-2920.13384
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bdellovibrio bacteriovorus from a tropical wastewater treatment plant and predation of mixed species biofilms assembled by the native community members

Abstract: It is reported here that a predatory bacterium belonging to the Genus Bdellovibrio, was isolated from activated sludge at the Ulu Pandan Water Reclamation Plant, Singapore. 16S rDNA gene sequencing analysis revealed that this isolate was 99% identical to 'Bdellovibrio bacteriovorus strain Tiberius' and hence is designated as 'Bdellovibrio bacteriovorus UP'. Using a novel approach based on fluorescence in situ hybridization (FISH), a prey cell density-dependent growth pattern of B. bacteriovorus UP was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
(41 reference statements)
2
25
0
1
Order By: Relevance
“…Floccular activated sludge has a function in the degradation of organic matter as well as the removal of nitrogen and phosphorus. Feng et al (2016Feng et al ( , 2017 demonstrated that these biofilms do not protect sensitive species from BALOs predation, with BALOs being able to penetrate and/or degrade the biofilm for access to its prey. Thus, the vast majority of Gram-negative bacteria within the sludge are sensitive to BALOs, irrespective of if they are planktonic or in biofilm.…”
Section: Balos Regulation Of Prey and Non-prey Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Floccular activated sludge has a function in the degradation of organic matter as well as the removal of nitrogen and phosphorus. Feng et al (2016Feng et al ( , 2017 demonstrated that these biofilms do not protect sensitive species from BALOs predation, with BALOs being able to penetrate and/or degrade the biofilm for access to its prey. Thus, the vast majority of Gram-negative bacteria within the sludge are sensitive to BALOs, irrespective of if they are planktonic or in biofilm.…”
Section: Balos Regulation Of Prey and Non-prey Biofilmsmentioning
confidence: 99%
“…This, in turn, led to a reduction of the preyassociated recombinant plasmid, limiting the chances for HGT. Predatory bacteria thrive in environments with high prey density, hence are naturally occurring in WWTPs (El-Shanshoury et al, 2016;Feng et al, 2016;Yu et al, 2017). Not only do they kill the prey, but they also completely degrade its DNA (Matin and Rittenberg, 1972;Rosson and Rittenberg, 1979), consequently reducing the pool of ARGs in the environment.…”
Section: Predatory Bacteria As a Strategy To Combat Horizontal Gene Tmentioning
confidence: 99%
“…More experimental approaches have been conducted to possibly modulate the WWTP microbiome, rather than specifically address the amounts of bacteria within the plant. Of those approaches, addition of bacteriophages to target specific bacteria ( Withey et al, 2005 ), as well as addition of predatory bacteria targeting Gram-negative bacteria specifically ( Feng et al, 2016 ), has been postulated. While both approaches offer a unique ability to modulate the microbiome, and remove planktonic as well as biofilm bacteria, their impact in spreading of antibiotic resistance has not been studied; neither has the stress they impose upon bacteria.…”
Section: Wastewater Treatment Plants As Hotspots For Antibiotic Resismentioning
confidence: 99%
“…Bdellovibrio and like organisms have a wide prey range (Stolp & Starr 1963;Jurkevitch et al 2000;Dashiff et al 2011;Feng et al 2016).…”
Section: Discussionmentioning
confidence: 99%